Vegan milk and egg alternatives commercialized in Brazil: A study of the nutritional composition and main ingredients - Romão, Bernardo; Botelho, Raquel Braz Assunção; Nakano, Eduardo Yoshio; Borges, Vinícius Ruela Pereira; de Holanda, Maria Eduarda Machado; Raposo, António; Han, Heesup; Gil-Marín, Miseldra; Ariza-Montes, Antonio; Zandonadi, Renata Puppin (Frontiers in Public Health, 2022)
Worldwide, there is an increasing demand for plant-based food due to sustainable, health, ethical, religious, philosophical, and economic reasons. In Brazil, 14% of the population declares themselves vegetarians, and a noticeable increase in the consumption of vegan products is also noted. Substitution of animal dairy and egg is challenging from both sensory and nutritional aspects. Yet, there are no data regarding the nutritional value and ingredients of Brazilian commercial dairy and egg substitutes. Therefore, this study aimed to analyze the nutritional composition and used ingredients in Brazilian commercial vegan alternatives to dairy and eggs to provide information for Brazilian consumers of these products. A cross-sectional quantitative study was carried out in three steps: (i) sample mapping. (ii) data collection, and (iii) statistical analysis. A total of 152 samples were included. No differences were found between the energy value and total fat of vegan products and their animal counterparts. Vegan products showed higher amounts of carbohydrates and dietary fiber, and only the vegan versions of beverages and cheeses showed less protein than their counterparts. Cashews, rice, coconut, and soy were the most used ingredients in dairy substitutes. Emulsions of oil, starch, and isolated protein were used in vegan egg products. Most vegan beverages presented sugar in their composition. Vegan alternatives of dairy and eggs might be suitable for substituting their animal counterparts, but given that traditional versions of cheeses and milk are sources of protein in omnivorous diets, for equivalent nutritional replacement in vegan products, it is necessary to improve the protein content of their vegan counterparts.